CORRELATION ANALYSIS OF INTEGRAL TRAINING IN 12-17-YEARS-OLD GYMNASTS - D.Kh.Umarov (Research Focus International Scientific Journal, 2023)
Correlational analysis materials made it possible to study the specific features of connection of various aspects of integral training of gymnasts with their sport and technical skills. The 20-order matrix was analyzed by the method of principal components, which includes individual indicators describing the training process of 12-17-year-old young gymnasts